Ontology-based semantic integration scheme for medical image grid. (18th December 2008) - Jin, Hai; Sun, Aobing; Zheng, Ran; He, Ruhan; , Qin Zhang
Ontology is becoming a key for grid platform to support the integration of heterogeneous resources by means of processing resource description and enactment. Medical Image Grid (MedImGrid) aims to access, archive and analyse medical data from distributed healthcare information systems to adapt to the development of healthcare information infrastructure. But the heterogeneities of those systems, especially the semantic gulfs, hamper their interoperations even encapsulated as web services in a grid environment. In this paper, we propose an ontology-based semantic integration scheme for MedImGrid, which adopts a hybrid method to create a MedImGrid semantic environment and unifies its information exchange model with Health Level 7 v3 protocol. The MedImGrid ontologies share the same lexicon to simplify the semantic transformation within a distributed environment. The ontology-based semantic integration components are also designed to support the semantic interoperations of MedImGrid. We test the performances of our scheme with simulation experiments to evaluate the feasibility of our approaches.